THE PROBLEM OF QUALITY DEFINITION AND QUALITY ASSURANCE IN SOCIAL SERVICES SECTOR IN LITHUANIA - ADOMAITYTĖ-SUBAČIENĖ, Ieva (Socialinė teorija, empirija, politika ir praktika, 2015)
The article examines different quality concepts and analyses the opportunities to implement those concepts into the social services sector. The author provides the context of social services sector in Lithuania by analysing the new challenges arising in this sector based on the need to implement quality assurance and quality assessment models. In accordance with the specifics of social work and the vulnerability of the social work client, it is important to define the role of internal quality model based on standardization, and the external one based on professional self-regulation and ethics. The article examines the quality of social services and the context of this definition in the Lithuanian strategic documents.
Keywords: quality of social services; quality assurance; quality management; definition of quality